PERLINDUNGAN HUKUM TERHADAP NASABAH BANK YANG DIRUGIKAN AKIBAT KEJAHATAN SKIMMING DITINJAU DARI PERSPEKTIF TEKNOLOGI INFORMASI DAN PERBANKAN - Ekawati, Dian (Universitas Ekasakti, 2018)
The progress of the banking system cannot be separated from the role of information technology. In addition to facilitating the company's internal operations, technology tools also aim to facilitate service to bank customers. One side of Information Technology provides not a few benefits to improving services both public services and internal services. On the other hand Information Technology is used by people who are not responsible by committing acts that are against the law, which attacks various legal interests of the people, society, and the state. This study aims to get information about banking crimes that use the skimming method and about legal protection for customers who are victims of skimming crime. The research method is juridical normative, namely obtaining and combining and analyzing data obtained from books, articles and journals and related legislation. The results obtained are that crime skimming is an old mode of customer money burglary which is done by stealing customer data at the customer's ATM with skimmer techniques. Legal protection against customers who are harmed due to the crime of skimming can be carried out by criminal means, namely reporting to the police and the police's duty to arrest the perpetrators. Legal protection through civil law by way of the bank replacing the customer's money after clarifying the transaction against the customer's account